2019
DOI: 10.1007/s12034-019-1848-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pyramid size on reflectivity of silicon surfaces textured using an alkaline etchant

Abstract: Surface texturing of p-type monocrystalline silicon (100) is well known as one of the best methods to reduce reflection losses and to increase light trapping and light absorption probability. Pyramid surface textures play a major role in reducing the reflectance of monocrystalline silicon surfaces. In this paper, the size of pyramids formed on the surface of p-type silicon substrates and by changing the etching characteristics during the texturing process of silicon were studied and evaluated. The pyramids tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Silicon, one of the most abundant materials on earth, is one of the most promising materials for solar cells in the current semiconductor industry. Additionally, the textured silicon substrate is well known for its low cost, high current efficiency, stable thermal properties, and excellent biocompatibility. , Therefore, it is a promising candidate for devices in optoelectronics, photovoltaics, , and biomimetic superhydrophobicity. Scientists have been working on the fabrication of textured silicon since the 1900s. For example, the pyramidal structure can improve the efficiency of photovoltaic cells since it can collect reflected light and trap the light inside the structure by multiple internal reflections. , …”
Section: Introductionmentioning
confidence: 99%
“…Silicon, one of the most abundant materials on earth, is one of the most promising materials for solar cells in the current semiconductor industry. Additionally, the textured silicon substrate is well known for its low cost, high current efficiency, stable thermal properties, and excellent biocompatibility. , Therefore, it is a promising candidate for devices in optoelectronics, photovoltaics, , and biomimetic superhydrophobicity. Scientists have been working on the fabrication of textured silicon since the 1900s. For example, the pyramidal structure can improve the efficiency of photovoltaic cells since it can collect reflected light and trap the light inside the structure by multiple internal reflections. , …”
Section: Introductionmentioning
confidence: 99%
“…In the case of monocrystalline silicon, a random upright pyramid texture, created by wet alkaline etching, is most commonly used. [15][16][17][18] This texture reduces reflectance and increases light trapping, and thus contributes to an increase in the current output of the solar cell 15,[19][20][21] and is also cheaper to realize than a perfectly planar substrate surface. In this paper, it is shown that such substrates coloured with single layer thin film coatings possess better angular colour stability than planar substrates coated with identical coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the fabrication of micro-nano structures on the silicon surface is a popular route for surface modification [14][15][16][17][18][19][20][21]. For example, pyramidal structures effectively reduce the surface's reflectivity and improve the efficiency of photovoltaic cells, which is attributed to their ability to collect and capture light through internal reflection [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%